Assessment of different sowing windows and crop geometry on fodder yield, quality and economics of dual-purpose sorghum (Sorghum bicolor) - SREE, YERRADODDI SINDHU; KARTHIKEYAN, R; BOOMIRAJ, K; DJANAGUIRAMAN, M; THIRUNAVUKKARASU, M; PAUL, R AROCKIA INFANT; JEEVAN, N; PRASANNA, JAKKU (The Indian Journal of Agricultural Sciences, 2026)
Sorghum [Sorghum bicolor (L.) Moench] is inherently drought-tolerant, however, escalating climate variability, intensifying environmental stresses, and widening fodder shortages underscore the critical need to refine sowing time and crop geometry to enhance productivity. Therefore, field experiments were conducted during summer and rainy (kharif) 2022 and winter (rabi) 2022–2023 seasons at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu to evaluate the effect of sowing window and crop geometry on yield and quality of dual-purpose sorghum (grain + fodder). The experiment was laid out in strip plot design (SPD) with three replications. Treatments included date of sowing as Factor I, i.e. First fortnight (I FN) of February, March and April months during summer 2022 season, I FN of May, June, July months during kharif 2022 season and II FN of August, September and October during rabi 2022–2023 season and six different crop geometries as Factor II, viz. 45 cm × 15 cm (S1); 45 cm × 10 cm (S2); 45 cm × 5 cm (S3); 30 cm ×15 cm (S4); 30 cm × 10 cm (S5) and 30 cm × 5 cm (S6). Results revealed that the crop sown in I FN of April with spacing of 30 cm × 5 cm recorded significantly the highest green fodder yield (35.5 t/ha) with low crude fibre, high total digestible nutrients (TDN). The study affirmed clear shift in yield and quality across multiple seasons and helps farmers in selecting the most productive planting time and crop geometry across seasons. The benefit-cost ratio was highest (2.63) when sowing was taken during April I FN along with 30 cm × 5 cm spacing compared to all other sowing windows in respective seasons.